As interações entre egressos e alunos do curso de Licenciatura em Química e suas potencialidades para a formação inicial de professores - Ocanha, Mariane (2021)
This study was part of a doctoral degree program in science teaching at Universidade Federal do Mato Grosso do Sul (UFMS). The investigation focused on initial chemistry teacher training, and it was based on Cultural Historical Theory and on Collaborative Research. Our aim was to analyze the potential emerging from the interactions and mediations that occurred between students and former students from the chemistry teaching course at Instituto Federal de Mato Grosso do Sul, Coxim campus (IFMS – Coxim), in order to help with initial chemistry teacher training. In this context, the research question is: What potential can the interactions and mediations between students and former students from the chemistry teaching course at IFMS-Coxim offer to initial chemistry teacher training? The research subjects were future teachers and former students from the chemistry teaching course at IFMS-Coxim. To carry out the research, we took a qualitative approach and applied the following methodologies: to produce the data, we held conversation circles; to analyze the data, we used collaborative research. During data analysis, we identified the following themes: interactions and mediations, a priori; collaboration and critical reflection clues, a posteriori. Based on these themes, we understood that chemistry teaching course students’ longings were fulfilled in terms of the course itself and the job market. Therefore, we conclude that the interactions and mediations between current and former chemistry teaching students – which were made possible through conversation circles – have great potential to help initial chemistry teacher training because they provide students with former students’ experience, thus enabling them to rethink their own formation process. Besides, it was possible to identify collaboration marks, which paved the way for the development of bonds beyond the university walls, and also evidence of critical reflection in order to overcome the barriers that are part of the initial teacher training process.